Description of First-Grade Students' Initial Reading Ability Based on The Early Grade Reading Skill Assessment (Egra) Test - Safitri, Novi; Heryani, Rina; Hidayat, Soleh (International Conference on Elementary Education, 2025)
Students' low initial reading ability often hinders their learning. Therefore, it is important to know the extent of students' early reading abilities so that any problems that arise can be addressed early on. This study aims to describe the initial reading abilities of first-grade students. Using a qualitative descriptive method, this study involved 60 students from two schools, as well as two first-grade teachers, to gain insight into the factors that hinder students' initial reading abilities in first grade. The initial reading test used the Early Grade Reading Skill Assessment (EGRA) instrument. The results showed that 80% of students still needed guidance, 12% of students were in the good category, and 8% were in the sufficient category. Based on the EGRA assessment indicators, the highest percentage was in letter recognition ability at 43%, while reading comprehension was the lowest at 8%. Other indicators included reading syllables at 34%, reading words at 28%, listening at 29%, and fluency at 19%. The factors causing low reading skills included students' low interest and motivation to read, insufficiently varied teaching strategies and media, a lack of facilities and infrastructure for reading instruction, and the role and support of parents at home. The implication of this research is to determine students' initial reading abilities and their contributing factors, so that strategic steps can be taken to address the low initial reading skills of elementary school students.